Уточненная методика определения тепловой производительности системы отопления с учетом неравномерности распределения параметров - Ганжа, Антон Николаевич; Братута, Эдуард Георгиевич; Марченко, Наталья Андреевна (НТУ "ХПИ", 2009)
The specified methodic for definition of real heat productivity of heaters and heating system taking into account unevenness of parameters distribution of heat carrier and inner air and executed alterations is making. By means of making methodic at realization of energetic audit of heating system can determine real heat productivity of heating systems, reveal point of heat over-expenditure and its low-quality issue and work out modernization recommendation.
Keywords: отопление; теплоснабжение; расход теплоты; теплоносители; конвектор; радиатор; температура воздуха; тепловая производительность